Incidence of Speech-Correcting Surgery in Children With Isolated Cleft Palate. (September 2018) - Gustafsson, Charlotta; Heliövaara, Arja; Leikola, Junnu; Rautio, Jorma
Objective: Speech-correcting surgeries (pharyngoplasty) are performed to correct velopharyngeal insufficiency (VPI). This study aimed to analyze the need for speech-correcting surgery in children with isolated cleft palate (ICP) and to determine differences among cleft extent, gender, and primary technique used. In addition, we assessed the timing and number of secondary procedures performed and the incidence of operated fistulas. Design: Retrospective medical chart review study from hospital archives and electronic records. Participants: These comprised the 423 consecutive nonsyndromic children (157 males and 266 females) with ICP treated at the Cleft Palate and Craniofacial Center of Helsinki University Hospital during 1990 to 2016. Results: The total incidence of VPI surgery was 33.3% and the fistula repair rate, 7.8%. Children with cleft of both the hard and soft palate (n = 300) had a VPI secondary surgery rate of 37.3% (fistula repair rate 10.7%), whereas children with only cleft of the soft palate (n = 123) had a corresponding rate of 23.6% (fistula repair rate 0.8%). Gender and primary palatoplasty technique were not considered significant factors in need for VPI surgery. The majority of VPI surgeries were performed before school age. One fifth of patients receiving speech-correcting surgery had more than one subsequent procedure. Conclusion: The need for speech-correcting surgery and fistula repair was related to the severity of the cleft. Although the majority of the corrective surgeries were done before the age of 7 years, a considerable number were performed at a later stage, necessitating long-term observation.